2002
DOI: 10.1093/alcalc/37.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Family Structure, Parent-Child Relationships, and Alcohol and Other Drug Use Among Teenagers in France and the United Kingdom

Abstract: This paper compares samples of 15-16-year-olds from the UK and France on their usage of alcohol, tobacco and illicit drugs and also seeks to describe the associations between alcohol and other drug use with "family variables" within the two countries. Compared to UK adolescents, French adolescents showed a slightly higher rate of cigarette smoking, were almost identical on cannabis use, rather lower on the use of other illicit drugs and very considerably lower on alcohol use. Family variables were related to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
131
6
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(166 citation statements)
references
References 23 publications
17
131
6
12
Order By: Relevance
“…Age differences in tobacco, alcohol, and drug use Consistent with prior research, we found that rates of adolescent alcohol use and abuse increase with age (Choquet et al, 2000;Ledoux et al, 2002). …”
Section: Comparison With Past Researchsupporting
confidence: 90%
See 2 more Smart Citations
“…Age differences in tobacco, alcohol, and drug use Consistent with prior research, we found that rates of adolescent alcohol use and abuse increase with age (Choquet et al, 2000;Ledoux et al, 2002). …”
Section: Comparison With Past Researchsupporting
confidence: 90%
“…In France, women perceive alcohol and drug use as more risky than men ) and women's substance use is less well accepted than men's (Ledoux et al, 2002). Yet it is notable that rates of alcohol and drug use in girls have been rising over time, resulting in the progressive narrowing of the sex gap .…”
Section: Sex Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been suggested that externalizing behavior in children may have a negative impact on parent-child communication and bonding (Reed & Dubow, 1997), which in turn has been found to be associated with the later use of illicit drugs by the children (Ledoux, Miller, Choquet, & Plant, 2002). Alternatively, children with a high level of externalizing behavior are more prone to drop out of school and to poor educational attainment (Moffitt & Silva, 1987), which may lead to early substance use (King et al, 2004), and in turn, be associated with CUD in early adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analytic evidence indicates that a positive parent-adolescent relationship predicts later initiation of alcohol use, and less problematic alcohol use later in life [14]. There is also evidence that parent-adolescent relationship quality predicts future use of tobacco, marijuana, and other illicit substances [15,16]. Moreover, intervention programs that improve the quality of the parent-child relationship have been shown to delay the onset and reduce the rate of substance use [17].…”
Section: Introductionmentioning
confidence: 99%